Effectiveness of Mokegi (Dental Health Monopoly) in Improving Knowledge of Dental Caries Among Preschool Children in Tulungagung - zenicxa ratria agustananda; Isnanto; Siti Fitria Ulfah (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2025)
Dental caries remains one of the most prevalent oral health problems among preschool children, largely driven by inadequate knowledge and poor oral hygiene habits. Preliminary assessments at TK B Dharma Wanita Talang II Tulungagung revealed that 42% of students possessed insufficient knowledge regarding dental caries, highlighting the need for engaging and developmentally appropriate educational interventions. This study aimed to evaluate the effectiveness of the Dental Health Monopoly (MOKEGI) game in improving preschool children’s knowledge of dental caries. A quasi-experimental pretest–posttest design with a control group was employed, involving 46 preschool children who were divided equally into intervention and control groups. Knowledge levels were measured using a validated and reliable questionnaire, and data were analyzed using the Wilcoxon signed-rank test and Mann–Whitney U test. The findings demonstrated substantial improvement in knowledge within the intervention group after exposure to the MOKEGI game, with all children (100%) achieving a “good” knowledge category post-intervention. In contrast, the control group showed only moderate improvement, with 56.5% reaching the “sufficient” category and none attaining the “good” category. Statistical results confirmed significant differences within the intervention group (p < 0.001) and between the intervention and control groups (p < 0.001). These outcomes indicate that MOKEGI is highly effective as an interactive, game-based educational tool for improving preschool children’s understanding of dental caries. In conclusion, the MOKEGI game provides an engaging and effective medium for enhancing oral health knowledge among young children and holds potential for integration into early childhood health education programs. Future research should assess long-term knowledge retention, behavioral changes, and applicability across diverse school settings.